2006
DOI: 10.1021/ja066522h
|View full text |Cite
|
Sign up to set email alerts
|

Facile Photochemical Synthesis of Unprotected Aqueous Gold Nanoparticles

Abstract: Aqueous, unprotected gold nanoparticles were prepared from HAuCl4 using a water-soluble benzoin (Irgacure-2959) as a photochemical source of strongly reducing ketyl radicals. This rapid method provides spatiotemporal control of nanoparticle generation, while light intensity can be used to control particle size. The particles are stable for months and do not require any of the conventional (S, N, or P) stabilizing ligands, although these can be readily incorporated if required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
283
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(291 citation statements)
references
References 22 publications
4
283
0
1
Order By: Relevance
“…Scaiano et al 2 reported a synthesis of unprotected aqueous gold nanoparticles prepared in minutes with a commercial photoreactor …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaiano et al 2 reported a synthesis of unprotected aqueous gold nanoparticles prepared in minutes with a commercial photoreactor …”
Section: Resultsmentioning
confidence: 99%
“…The preparation of gold nanoparticle (GNP) following the procedure described in literature 2 . Briefly, 0.33 mmol L -1 gold (III) chloride trihydrate (HAuCl 4 .3H 2 O) was mixed with 1.0 mmol L -1 Irgacure™ (1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one) I-2959 in water.…”
Section: Preparation Methods Of Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AuNPs are often stabilized by thiol-capping agents (Yu and Irudayaraj 2007 ) that impart negative or positive charges to the particles. The reduction of the metal salt can be carried out electrochemically (Plieth et al 2005, Huang et al 2006a, 2007, Starowicz et al 2006, photochemically (Pillai and Kamat 2004, McGilvray et al 2006, Sakamoto et al 2007, sonochemically (Jiang et al 2004, Park et al 2006, or using chemical reductants such as citrates (Pillai and Kamat 2004 ), hydrides (Kariuki et al 2004, Pal et al 2007, alcohols (Wiley et al 2004 ), hydrogen (Evanoff and Chumanov 2004 ), hydroxylamine ), or hydrazine (Shi et al 2006 ). By choosing a specific reductant, stabilizer, temperature, and concentrations of the reactants, the shapes and sizes of the NPs can be controlled, as shown in Figure 2 .…”
Section: Synthesis/fabrication and Functionalization Of Aunp Probesmentioning
confidence: 99%
“…For synthesis of spherical AuNPs, besides a reducing agent, an additional stabilizing or capping agent is sometimes added to the reaction mixture to prevent the AuNPs from aggregating. McGilvray et al (2006), 9 reported a simple and rapid photochemical synthesis of AuNPs to obtain monodisperse spherical nanoparticles that are stable in suspension. In this synthesis, the reduction of Au (III) was achieved by ketyl radicals generated due to the UVA-irradiation of Irgacure-2959 (Irg), a photoinitiator.…”
mentioning
confidence: 99%